Adjuvant Potential of Selegiline in Attenuating Organ Dysfunction in Septic Rats with Peritonitis - Tsao, Cheng-Ming (Public Library of Science, 2014)
Selegiline, an anti-Parkinson drug, has antioxidant and anti-apoptotic effects. To explore the effect of selegiline on sepsis, we used a clinically relevant animal model of polymicrobial sepsis. Cecal ligation and puncture (CLP) or sham operation was performed in male rats under anesthesia. Three hours after surgery, animals were randomized to receive intravenously selegiline (3 mg/kg) or an equivalent volume of saline. The administration of CLP rats with selegiline (i) increased arterial blood pressure and vascular responsiveness to norepinephrine, (ii) reduced plasma liver and kidney dysfunction, (iii) attenuated metabolic acidosis, (iv) decreased neutrophil infiltration in liver and lung, and (v) improved survival rate (from 44% to 65%), compared to those in the CLP alone rats. The CLP-induced increases of plasma interleukin-6, organ superoxide levels, and liver inducible nitric oxide synthase and caspase-3 expressions were ameliorated by selegiline treatment. In addition, the histological changes in liver and lung were significantly attenuated in the selegiline -treated CLP group compared to those in the CLP group. The improvement of organ dysfunction and survival through reducing inflammation, oxidative stress and apoptosis in peritonitis-induced sepsis by selegiline has potential as an adjuvant agent for critical ill.